Utilização de creatinina e potássio sérico como ferramenta de busca de fatores que predispõe a ocorrência de IRA e hipercalemia - Pellissari, Rafaela Sonsim de Oliveira (2021)
In the hospital environment, the occurrence of adverse drug events (ADE) is frequent, and monitoring is essential to prevent or reduce more serious harm to patients and reduce wasted resources. The identification of an ADE can be performed using trackers, which are considered an effective method of monitoring Trackers are groups of specific medications / antidotes, signs and symptoms or laboratory tests that signal in a timely manner or harm to the patient. Among them, the exams of serum creatinine and potassium stand out. Due to the increasing number of hospital patients with acute kidney injury (AKI) and hyperkalemia, monitoring these tests is essential. Objective: To identify predisposing factors to adverse renal events through creatinine and serum potassium tests. Methods: This is an observational study of the historical cohort type, applying the medical record review technique, from July to December 2019 in a large university hospital in southern Brazil. Inclusion criteria were patients over 18 years old from the medical/surgical, emergency orthopedics and orthopedics/neurology sectors. Patients without serum creatinine and potassium test results, with a hospital stay of less than 72 hours, with a previous history of kidney disease and transfer to sectors not included in the study were excluded. According to the criteria of KDIGO - Acute Kidney Injury Work Group (2012) and European Resuscitation Council Guidelines for Resuscitation (2015), patients who developed AKI and hyperkalemia, respectively, during the hospitalization period were identified. Statistical analyzes were performed using the Kolmogorov-Smirnov test, Shapiro-Wilk, graph inspection and Pearson correlation, considering statistically significant p≤0.05 to search for the factors that predispose these diseases. Results: 638 medical records were analyzed, of which 138 were excluded for not meeting the eligibility criteria, leaving 500 patients for analysis. Of these, 29 patients developed AKI during the hospital stay, 19 in stage one, four in stage two and six in stage three. For hyperkalemia, 13 patients developed this event, six in mild stage, six moderate and one severe. Of the patients who developed AKI, 72.4% were male, with an advanced mean age of 59.9±15.3 years, p=0.025 and length of stay with a median of 11 (IIQ 6), p≤0 and for those who developed hyperkalemia, 53.8% were male, mean age 67.2±15.8 years, p=0.004 and longer hospital stay with a median of 15 (IIQ21), p=0.002. Comorbidities anxiety and diabetes mellitus (DM) were statistically significant for the development of AKI and hyperkalemia. The drugs related to AKI were vancomycin, piperacillin+tazobactam, carvedilol and meropenem and for hyperkalemia, spironolactone, acetylsalicylic acid and carvedilol. Conclusion: The factors identified for predisposition to AKI and hyperkalemia were: male gender, advanced age, longer hospital stays, presence of comorbidities, and the use of some medications. This evidence reinforces the importance of monitoring serum tests and the rational use of drugs in the hospital environment by the health team.